Compact Digital Television (DTV) Antenna for Indoor Usage - Mohamad Aasyraaf Mohd Shaufi; Huda A. Majid; Zuhairiah Zainal Abidin; Samsul Haimi Dahlan; Mohamad Kamal A. Rahim; Osman Bin Ayop (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A compact indoor digital antenna for digital terrestrial television is proposed. The design of the antenna begins with the material selection to construct the antenna by using CST software with a standard monopole antenna design. The antenna is then simulated and optimized. A bandwidth of 290 MHz (46.14%) between 500 MHz and 790 MHz is achieved with the antenna gain more than 3 dBi. Simulated results is used to demonstrate the performance of the antenna. The simulated return losses, together with the radiation patterns and gain are presented and discussed.